Public Space As A Medium Of Communication In Chennai Metropolitan Area With Socio-Cultural Context - et. al., Mr. Salai Tamilarasan. S, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research is dedicated to the people’s role and perception of public space and discusses the social life of people in public spaces with socio-cultural context of Chennai Metropolitan Area. Chennai is considered to be one of the multicultural cities with a very high volume of immigrant people and also provides a research context in various ways, in the present world the role of public spaces in social life has become more important. A qualitative study approach was used and the method focused on the study was a review of documents and maps, surveys, observations and interviews. This research raises the question that how public spaces help people to have interaction and how it helps them in social connection. Initially, it describes the clear information about Chennai and its public spaces. Thereafter, the study addresses the socio-cultural context from the human perspective. The aim of the work is to analyze that how public space connects people to have a social interaction and also to analyze the perspective of people about the public space. At end, the author tries to answer the question: would public space create a cultural communication? In the conclusions, the aim of the research is explained and new research directions are indicated for further research process.